2017
DOI: 10.3389/fphar.2017.00779
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Properties of Chronic Antidepressant Drugs Treatment on the Brain Chemokine – Chemokine Receptor Network: A Molecular Study in an Animal Model of Depression

Abstract: An increasing number of studies indicate that the chemokine system may be the third major communication system of the brain. Therefore, the role of the chemokine system in the development of brain disorders, including depression, has been recently proposed. However, little is known about the impact of the administration of various antidepressant drugs on the brain chemokine – chemokine receptor axis. In the present study, we used an animal model of depression based on the prenatal stress procedure. We determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 81 publications
2
33
0
1
Order By: Relevance
“…injection of LPS or IL-1β, and to affect the central balance between pro- and anti-inflammatory cytokines (IL-1β/IL-10) [ 29 ]. In line with our previous data, we demonstrated that tianeptine has the ability to diminish depression-like behavior (in an animal model of depression) via normalization of the IGF-1 family network, as well as through cytokines and the chemokine/chemokine receptor axis [ 30 , 31 ]. Among others, chronic tianeptine treatment diminished malfunction in the fractalkine (CX3CL1) and fractalkine receptor (CX3CR1) axis.…”
Section: Introductionsupporting
confidence: 90%
“…injection of LPS or IL-1β, and to affect the central balance between pro- and anti-inflammatory cytokines (IL-1β/IL-10) [ 29 ]. In line with our previous data, we demonstrated that tianeptine has the ability to diminish depression-like behavior (in an animal model of depression) via normalization of the IGF-1 family network, as well as through cytokines and the chemokine/chemokine receptor axis [ 30 , 31 ]. Among others, chronic tianeptine treatment diminished malfunction in the fractalkine (CX3CL1) and fractalkine receptor (CX3CR1) axis.…”
Section: Introductionsupporting
confidence: 90%
“…Accordingly, experimental approaches using diverse types of stress are considered useful animal models to simulate this condition [ 240 ]. In the article by Trojan et al [ 231 ], prenatal stress caused anxiety and depressive-like disturbances in the adult offspring of rats. The changes were followed by the reduction in CX3CL1-CX3CR1 expression in the hippocampi and the frontal cortices of these animals.…”
Section: The Roles Of Cx3cl1-cx3cr1 and Cd200-cd200r Axes Malfunctionmentioning
confidence: 99%
“…The changes were followed by the reduction in CX3CL1-CX3CR1 expression in the hippocampi and the frontal cortices of these animals. The chronic administration of the antidepressants (tianeptine and fluoxetine) normalized the observed alterations both on the behavioural and biochemical levels [ 231 ]. Additionally, the intracerebroventricular application of exogenous CX3CL1 alleviated the changes in the behaviour and in the inflammatory processes observed in the brains of prenatally stressed rats [ 241 ].…”
Section: The Roles Of Cx3cl1-cx3cr1 and Cd200-cd200r Axes Malfunctionmentioning
confidence: 99%
“…Furthermore, selective serotonin and serotonin norepinephrine reuptake inhibitors (SSRI and SNRI, respectively) have been shown to reduce the inflammatory responses of microglia [90][91][92]. In addition, they are able to induce a ramified morphology and increase CX3CR1 expression [93][94][95]. It is not known yet whether antidepressants target the other markers differently expressed in MDD, such as TMEM119, CD163 and CD14.…”
Section: Potential Causes Of This Distinct Microglial Signaturementioning
confidence: 99%